The Effect Of Guided Note Taking Learning Model Using Macromedia Flash 8 On Students' Chemistry Learning Outcomes On The Periodic System Of Elements In Grade X - Lidya Marwaty Haloho; Eva Pratiwi Pane; Anita Debora Simangunsong (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This research or study aims to determine the effect of the Guided Note Taking Learning Model Using Macromedia Flash 8 on Student Chemistry Learning Outcomes on the Periodic System of Elements for Class X at SMA Kampus Nommensen Pematangsiantar. This type of research is experimental research using a pre-test and post-test research design. The population of this study was all class X of SMA Swasta Kampus Nommensen Pematangsiantar consisting of 3 classes. The sample taken was a random sampling technique. The sample in this study was students in class X - 1 as the experimental class and students in class X - 3 as the control class. Data on learning outcomes can be collected using an instrument in the form of an objective test in the form of multiple choice consisting of 25 questions. Furthermore, the data analyzed by testing the research hypothesis using the independent sample t-test using SPSS 24 was obtained based on the results of the hypothesis test data from learning outcomes with sig (2tailed) of 0.000 < 0.005, then H0 can be rejected and Ha accepted. And there is also data analyzed using the N-Gain test from learning outcomes showing an average value in the experimental class of 73% while the average value in the control class was 43%. This means that there is a significant difference in the guided note taking learning model using macromedia flash 8 on students' chemistry learning outcomes in the periodic system of elements material in class X of SMA Swasta Kampus Nommensen Pematang Siantar in the 2024/2025 Academic Year.